Subversive : Praktiken = Practices : Kunst unter Bedingungen politischer Repression 60er - 80er / Südamerika / Europe = Art under Conditions of Political Repression 60s - 80s / South America / Europe - Christ, Hans D.; Dressler, Iris; Württembergischer Kunstverein Stuttgart, Stuttgart (Stuttgart : Hatje Cantz Verlag Ostfildern-Ruit Württembergischer Kunstverein Stuttgart, 2009)
Alekseev, Nikita ; Altamirano, Carlos ; Altorjay, Gabor ; Angulo, Lucy ; de Aquino, Angelo ; Arias Vera, Luis ; Auto-Perforations-Artisten ; Barrio, Artur ; Bernea, Horia ; Bofill, Ricardo ; Brendel, Micha ; Burga, Teresa ; C.A.D.A. ; Carrión, Ulises ; Chatrny, Dalibor ; Chocano, Leonor ; Claus, Carlfriedrich ; Corazón, Alberto ; Csernik, Attila ; Dammbeck, Lutz ; Deisler, Guillermo ; Die Gehirne ; Dittborn, Eugenio ; Downey, Juan ; Eielson, Jorge ; Elagina, Elena ; Erdély, Miklós ; Evangelista, Roberto ; Flondor, Constantin ; França Cocchiarale, Fernando ; Ginzburg, Carlos ; Giralt-Miracle, Daniel ; Grigorescu, Ion ; Hänsel, Claus ; Hastings, Rafael ; Herkenhoff, Paulo ; Hernández Saavedra, Emilio ; Huber, Joseph W. ; Ilie, Pavel ; Indigo ; IPUT ; Kanal X ; Kiraly, Iosif ; Kizeval'ter, Georgij ; Kocman, Jiri H. ; Lee, Leslie ; Leppe, Carlos ; de Magalhães, Gastão ; Maguiña, Ernesto ; Makarevic, Igor ; Manigk, Oskar ; Mariotti, Francesco ; Marquez, Alfredo ; Meissner, Norbert ; Mezza, Gonzalo ; Möllendorf, Yvonne von ; Monastyrsky, Andrei ; Muntadas, Antoni ; Neagu, Paul ; Nicolai, Olaf ; Olhagaray, César ; Padin, Clemente ; Panitkov, Nikolaj ; Parente, Leticia ; Parra, Catalina ; Pauer, Gyula ; Pazos, Luis ; Perjovschi, Dan ; Plaza, Julio ; Podsiadly, Féliks ; Portabella, Pere ; Pozzi-Escott, Mario ; Rabanal, Consuelo ; Rehfeldt, Robert ; Rodriguez, Herbert ; Romasko, Sergej ; Romero, Juan Carlos ; Rosenfeld, Lotty ; Ruiz Durand, Jesus ; Salazar, Juan Javier ; Salazar del Alcazar, Hugo ; Sau-Kerle ; Scherstjanoi, Valeri ; Schleime, Cornelia ; Sigma ; Stjoby, Tamás ; Stembera, Petr ; Stötzer, Gabriele ; Taller de Arquitectura ; Vater, Regina ; Vazquez Montalban, Manuel ; Vicuña, Cecilia ; Vigo, Edgardo Antonio ; Wodiczko, Krzysztof ; etc.
Biog. auteurs p. 564-571, bibliog. p. 571-576
Publication on the occasion of the exhibition 'Subversive : Praktiken = Practices' am Württembergischer Kunstverein Stuttgart in Stuttgart, 30.05.2009 - 02.08.2009
boek